Implementation of Value Clarification Technique to Build Students' Socio-Religious Character in Fiqh Learning at Ma'had Ibad Ar-Rahman Junior High School Surabaya - Muchammad Muwafa Azmi; Muhammad Arfan Mu’ammar; Asrori Asrori (Journal of Educational Sciences, 2026)
Fiqh learning is not only oriented toward the understanding of Islamic legal principles but also plays a role in shaping students’ socio-religious character. The subject of qurban in fiqh learning has considerable potential for internalizing values of sincerity and social concern. This study aims to describe the implementation of the Value Clarification Technique (VCT) in qurban fiqh learning and its contribution to the development of students’ socio-religious character at Ma’had Ibad Ar-Rahman Surabaya. This research employed a qualitative approach using field research with a case study design. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that the implementation of VCT through the stages of value stimulation and value clarification was able to enhance students’ active participation, social awareness, and understanding of religious values. However, the value reflection stage was not optimally implemented, resulting in partial internalization of values. Therefore, strengthening the reflection stage is necessary to support a more comprehensive development of students’ socio-religious character.